Hajj Fund Investment Management in Indonesia - Hulwati, Hulwati; Andespa, Roni; Mujiono, Slamet (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
Does the management of investment in Hajj funds in Indonesia impact the economy and welfare of the pilgrims in Indonesia? This study aims to see how the management of hajj funds in Indonesia. This research is motivated by the phenomenon of Hajj funds' investment management pattern that is applied in Indonesia. The location of this research is in Indonesia, where most of the population is Muslim. This study uses a qualitative approach. Data collection techniques used are through interviews and documentation. Interviews were conducted with the Hajj fund manager at the Indonesian Ministry of Religion, the Badan Pengelola Keuangan Haji (BPKH), and Bank Syariah Mandiri. Hajj funds managed by BPKH are placed on deposits and investments in securities. BPKH has now developed a hajj fund, and the investment returns positively impact the welfare of the hajj. The management of hajj funds through investment is the right way to benefit the congregation and for the welfare and benefit of the congregation during the pilgrimage. The return on investment is a government subsidy for pilgrims or covers the difference between the total cost of organizing the pilgrimage and the deposit paid by prospective pilgrims to the government. Pilgrims themselves can feel the subsidies provided through the management of hajj funds.